THE UNKNOWABILITY AND THE INEFFABILITY OF GOD ACCORDING TO JOHN SCOTT (ERIUGENA) (Annual of the Faculty of Philosophy in Skopje, 2019)
The paper explores the negative theology employed in John (Scott) Eriugena’swork “On the division of nature” as a core structure in his ontological system.Apophatic stances are crucial in Eriugena’s exposition of the position and role ofGod, and thus in the intricate functioning of the four divisions of nature and hisconcept of the five modes of interpretation of being. The basic categories in his systemof nature are shown, along with the most poignant claims of the ineffability andunknowability of God, in order to then analyse his framework of kataphatic and apophatictheologies in approaching the inaccessible, super-essential, incomprehensiblenature of the divinity. Eriugena’s opinions on the values and workings of the twobranches of theology place them not in conflict or disagreement with one another,but as complementary and in constant harmony. A major part of the paper dealswith Eriugena’s preference for the negations of the apophatic theology when talkingabout God, paired with an obvious awareness that the merits of the kataphatic theologyare also substantial in expressing a trace of God as a manifestation in the createdworld; as well as with his dialectical manoeuvre of stressing the significance ofthe more-than formulateons for God’s super-essentiality. Therefore, Eriugena’s ideason the formulae that are affirmative in form, but negative in meaning will be overviewed,in order to show his take on the advantages of the synthesis of the kataphaticand the apophatic theologies, in the form of a “hyperphatic” theology expressing Godas non-expressible (because more-than-expressible).
Keywords: ERIUGENA; GOD; APOPHATIC; KATAPHATIC; MORE-THAN; INEFFABIITY